2022
DOI: 10.3390/children9050601
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Psychological Derailment in Chinese Adolescents and the Mechanism by Which It Affects Mental Health: A Mediated Moderation Model

Abstract: Psychological derailment refers to the phenomenon whereby original self-expectations are seriously inconsistent with developments in reality. Research to date has neglected the valence of derailment and the mechanism by which it affects mental health. To improve the mental health of Chinese adolescents from the perspective of psychological derailment, after validating the translated Chinese versions of the derailment measurement instruments, we conducted an empirical study on the freshmen in senior high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In addition, freshmen newly admitted to a school should be given special consideration, as they are more likely to encounter difficulties in adapting to their new environment and to feel lost, which will increase their anxiety. Studies showed that Chinese adolescents are vulnerable to psychological derailments when they start a new period of school life (e.g., entering senior high school or college), which may lead to mental health problems, such as depression [ 38 ]. Investigations of the academic burden of Chinese students also suggested that during transition periods of school stages, students are more sensitive to the school workload, and thus, need more guidance on psychological adjustment and pressure management [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, freshmen newly admitted to a school should be given special consideration, as they are more likely to encounter difficulties in adapting to their new environment and to feel lost, which will increase their anxiety. Studies showed that Chinese adolescents are vulnerable to psychological derailments when they start a new period of school life (e.g., entering senior high school or college), which may lead to mental health problems, such as depression [ 38 ]. Investigations of the academic burden of Chinese students also suggested that during transition periods of school stages, students are more sensitive to the school workload, and thus, need more guidance on psychological adjustment and pressure management [ 39 ].…”
Section: Discussionmentioning
confidence: 99%